Pengaruh Keterlibatan Karyawan, Job Design, Flexible Working Arrangement, Work Engagement terhadap Kinerja Karyawan pada Karyawan Freelance Wedding dan Event Organizer - Mita Rahayu; Lukluk Atul Hidayati; Muhdiyanto (Jurnal Syntax Admiration, 2024)
This research aims to examine the influence of employee involvement, job design, flexible working arrangements, and work engagement on employee performance. The sample for this research is freelance wedding organizer and event organizer employees in Magelang. The sampling method uses purposive sampling with a total of 100 respondents. The data analysis technique used in this research uses multiple linear analysis which is processed using SPSS version 25 software. The results of this research show that employee involvement, job design, flexible working arrangements, and work engagement simultaneously influences employee performance. Meanwhile, in the individual analysis, employee involvement, job design, flexible working arrangements and work engagement directly have a positive and significant effect on employee performance.